A Play Sports Learning Approach can Improve Students' front Rolling Skills - Ganie Tri Lestari; Yudha Munajat Saputra; Anin Rukmana (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2024)
The aim of this research is to find out how the process and results of implementing playing sports learning affect students' forward rolling skills. The type of research used is classroom action research (Action Research Classroom). The classroom action research model used in this research is the Kemmis-Mc spiral model. This model divides one cycle of classroom action research procedures into four stages, namely planning, acting, observing and reflection. The research subjects were 26 students in class VI B at SDN Cicalengka 07 for the 2023/2024 academic year, consisting of 12 male students and 14 female students. The findings that can be shown in cycle I resulted in the complete achievement of the front roll skill results using playing sports learning at 70% with student activity at 74%. In cycle II, quite significant results were obtained in terms of completeness achievement of 85% with student activity of 88%. In cycle III, significant results were obtained in achieving completeness of 93% with student activity of 96%. It can be concluded from the research that through a playing sports learning approach it can improve students' forward rolling skills and activity.